Tensiones infantiles en el área afectiva - Ganazhapa Guamán, Mayra Lisseth (2017)
The present project is focused on the children's tensions in the affective area that influence the school integration, it was analyzed if the tensions affect the social development among the students of the first year of EGB of "Once de Noviembre" High school. Through the research could be identified the most common problems of the first-year children in social affective development, as well as a playful model to rescue values, attitudes and virtues that children should possess and put into practice whether in the classroom or anywhere. In this were involved parents, teachers and students, in which were used field research methodology applied and bibliography using quantitative data collection instruments such as the survey, but above all, they provided pedagogically with knowledge that stimulate socialization among children, as well as, contribute to the inclusion that today society needs it and educational work enters a meaningful education....